2019
DOI: 10.1017/aog.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of elastic moduli from seismic diving-wave and ice-core microstructure analysis in Antarctic polar firn

Abstract: We compared elastic moduli in polar firn derived from diving wave refraction seismic velocity analysis, firn-core density measurements and microstructure modelling based on firn-core data. The seismic data were obtained with a small electrodynamic vibrator source near Kohnen Station, East Antarctica. The analysis of diving waves resulted in velocity–depth profiles for different wave types (P-, SH- and SV-waves). Dynamic elastic moduli of firn were derived by combining P- and S-wave velocities and densities obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 64 publications
3
26
0
Order By: Relevance
“…The directional dependence of the seismic velocity, i.e. the seismic anisotropy of the firn, can also be determined by acquiring seismic data in different horizontal directions (Kirchner and Bentley, 1979, 1990; Schlegel and others, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The directional dependence of the seismic velocity, i.e. the seismic anisotropy of the firn, can also be determined by acquiring seismic data in different horizontal directions (Kirchner and Bentley, 1979, 1990; Schlegel and others, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Under creep conditions, Theile et al (2011) simulated intragranular deformations and microstructural changes and concluded a measurable impact of the crystallographic anisotropy on the densification of structurally isotropic snow. Back to polar firn conditions, recent measurements of seismic diving waves at Kohnen (Schlegel et al, 2019) indicated the necessity of quantifying the crystallographic fabric alongside with the structural fabric to evaluate uncertainties in the inversion technique giving access to the elastic moduli in firn cores.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the subglacial water pathways, we used a simple flux routing scheme to compute subglacial water pathways as described in Humbert et al (2018). Subglacial water flow is governed by the hydraulic potential (Shreve, 1972), which can be written as…”
Section: Routing Of Subglacial Watermentioning
confidence: 99%
“…Assuming α does not change over the travel path, A 0 can be calculated. As our geophones are vertically orientated and the direct wave is a diving wave (a continuously refracted wave due to the continuous densification of the firn pack; Schlegel et al, 2019), we used pairs of traces at larger offsets (97 m and larger) from the source, which causes the ray path of the diving wave to arrive at angles closer to normal incidence.…”
Section: Determination Of the Source Amplitude Amentioning
confidence: 99%